GENAS: a database system for nucleic acid sequence analysis. - Kuhara, S (1984)
A database system, named GENAS (GENe Analyzing System), for computer analysis of sequence was constructed using Adbis which is a relational database management system (1). GENAS enables us to retrieve any sequence data from EMBL nucleotide sequence data library (2) and readily to analyze them (if necessary, together with private data) by various application programs in a interactive manner. Analysis of structure of replication origin of replicons was demonstrated using this system.